Issuing process of a SME corporate bond using the example of Karlsberg Brauerei GmbH - Väth, Katharina Michele (2018)
Fil: Väth, Katharina Michele. University of Applied Sciences Hochschule Kaiserslautern. Faculty of Business Administration; Alemania.